Fusion Energy - Shahzad, Aamir (IntechOpen, 2020)
This book highlights the need for environmentally friendly energy sources. One of the most significant problems facing civilization today is how to generate alternative clean energy sustainably and in sufficient quantity to supply a growing global population. Fossil fuel burning machines pollute the atmosphere resulting in global warming and causing health risks. Alternatively, fusion energy does not produce any carbon dioxide. This book discusses the latest developments and innovative techniques of fusion energy and its practical uses. Chapters cover such topics as beam injectors for fission reactors, detachment in helical fusion devices, wave instabilities in dusty plasmas of fusion devices, tungsten-based plasma materials, migration energy by high-voltage electron microscopes, and taxonomy of big nuclear chambers.